Data communications and networks - Brewster, R. L. 1932- (Ronald L.) (Institution of Engineering and Technology, 1994)
The book is divided into thirteen chapters: introduction and overview; data over analogue systems; OSI seven-layer model; data transmission standards and interfaces; ISDN; broadband ISDN; basic LAN structures; protocols above the medium access layer; wide area networking; second generation LANs and MANs; data services over cellular radio; broadcast systems with data capability; and image networks.